Design and analysis of cryptographic algorithms in blockchain - Huang, Ke, 1989-; Mu, Yi, 1955-; Rezaeibagha, Fatemeh; Zhang, Xiaosong, 1968- (Boca Raton, FL : CRC Press, 2021)
"This book seeks to generalize techniques and experiences in designing and analyzing cryptographic schemes for blockchain. In addition, it covers surveys of research objects, reviews of cryptographic schemes, lectures and methodologies to practice cryptography"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Data encryption (Computer science); COMPUTERS / Computer Science; MATHEMATICS / Arithmetic; COMPUTERS / Computer Engineering